Investigation of antimicrobial prescribing patterns In general practices in Northern Ireland: National study - Ahmed Abuelhana; Eimear Clifford; Aaron Courtenay (Journal of Global Antimicrobial Resistance)
AIM: The primary aim of the study was to investigate antimicrobial prescribing patterns in General Practices (primary medical centres) in Northern Ireland. A secondary aim was to evaluate the prescribed antibiotics against WHO's AWaRe classification and prescribing targets. BACKGROUND: Antimicrobial resistance (AMR) is a global health threat estimated to cause ten million deaths worldwide by 2050, exceeding that of cancer. AMR primarily resulting from suboptimal antimicrobials use and in appropriate prescribing. METHOD: A retrospective, cross-sectional quantitative study was designed to measure and analyse the antimicrobial prescribing patterns within 325 GP practices across all Northern Ireland for 6 months, using open access BSO data* (Business service organisation). BSO data contains concise accurate records for all prescriptions in primary care Northern Ireland. RESULTS: A total of 3,168,775.38g of antibacterial drugs were prescribed in primary care throughout the duration of study. Penicillins were the most prescribed class (59.79%), followed by tetracyclines (10.68%) and macrolides (9.53%) (Table1, Figures1,2). Access group antibiotics were the most frequently prescribed (79.35%), followed by Watch group antibiotics (20.64%), with Reserve group antibiotics equating to nearly 0.01% as being occasionally prescribed. Derry GP federation (27 practices) prescribed the greatest amount of antibiotics overall in Northern Ireland (10.90%) (table2, Figure2). CONCLUSION: Despite meeting World Health Organisation (WHO) targets, GP practices within Northern Ireland must do more to further reduce antimicrobial consumption. Therefore, strategies such as increased communication between colleagues and supportive measures must be implemented within GP practices to enhance antimicrobial stewardship (AMS) across Northern Ireland and reduce potential resistance.